(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: Iron overload is the most common complication of ß- thalassemia thatcauses morbidity and mortality in children so chelating drugs are essentials forpreventing such complication. Oral deferasirox has a good safety and tolerance tomaintain ferritin level in non-toxic levels that affect heart and liver. Patients andmethods: A cohort retro - prospective study of eighty five patients 45 male(53%), 40female (47%), age from 2-18 years old, with ß-thalassemia who receiving deferasiroxin thalassemia center in Kirkuk city north of Iraq from the first of March to the end ofOctober 2016; that assessed by interview questionnaire, previous documents in thecenter and laboratory investigations for serum creatinine, serum ferritin and liverenzymes. Results: Adverse effects were shown in eight patients (9.4%), each of two(25%) had abdominal pain, increase appetite, and hair loss consecutively, allergy andnervousness in each one patient(12.5%) serum ferritin was decreased below thebaseline in 47 (55.3%), serum creatinine was elevated above the baseline in 22(25.8%) within normal levels, Elevated serum alanine transferase in 16 (18.8%), totalserum bilirubin was elevated in 14(16.6%) of all children; while serum aspartatetransferase elevated in 22(25.8%) of the normal eventually serum alkalinephosphatase was elevated in 22(25.8%). Conclusion: Deferasirox is well tolerated asan iron chelating with suitable dose and long duration has less adverse effects and canbe adjusted by dose modification.